An artificial CO-releasing metalloprotein built by histidine-selective metallation1. Issue 19 (7th March 2015) - Albuquerque, Inês S.; Jeremias, Hélia F.; Chaves-Ferreira, Miguel; Matak-Vinkovic, Dijana; Boutureira, Omar; Romão, Carlos C.; Bernardes, Gonçalo J. L.
<x xml:space="preserve">Abstract</x> We report the design and synthesis of an aquacarbonyl Ru(ii) dication cis-[Ru(CO)2(H2O)4]2+ reagent for histidine (His)-selective metallation of interleukin (IL)-8 at site 33.